Iridocorneal Endothelial Syndrome - Sitoula, Rakshya Panta (Journal of Nobel Medical College, 2015)
The iridocorneal endothelial (ICE) syndrome is characterized by abnormalities of the corneal endothelium, iris, and anterior segment leading to secondary angle closure glaucoma. ICE syndrome is usually unilateral, nonheritable and most common in white women in the third to fifth decades.Journal of Nobel College of Medicine Vol.4(1) 2015: 64-65